Misconceptions about transmission, symptoms and prevention of HIV/AIDS among adolescents in Ebonyi state, South-east Nigeria - Agu, Ifunanya Clara (BMC Res Notes, 2020)
OBJECTIVES: Nigeria has the second largest number of adolescents and young people living with HIV/AIDS in the world. Misconceptions about HIV/AIDS contribute to spread of HIV, and constrain uptake of preventive services. This paper explored misconceptions about HIV/AIDS among adolescents in south-east Nigeria. A qualitative study was conducted in six urban and rural local government areas of Ebonyi state. Data were collected through twelve focus group discussions (FGD) with unmarried adolescents aged 13–18 who were either attending school or out-of-school. The FGDs were conducted using a pre-tested topic guide. Data were coded manually and analyzed using a thematic framework approach. RESULTS: There are persistent misconceptions about transmission of HIV/AIDS through mosquito bites and sharing of personal belongings. Some adolescents had inaccurate notions that a HIV infected person could be identified through changes in physical features such as abdominal swelling and longer fingernails. A few of them also reported that HIV could be treated with antibiotics. These misconceptions were expressed by both male and female adolescents. Adolescents have some mistaken beliefs about HIV/AIDS which constrain them from taking necessary preventive measures. Hence, the need to target adolescents with health education interventions on HIV/AIDS.